2018
DOI: 10.1002/ejlt.201800210
|View full text |Cite
|
Sign up to set email alerts
|

Development of Methods Used in the Extraction of Avocado Oil

Abstract: Avocado oil contains high concentrations of unsaturated fatty acids and many health‐promoting beneficial compounds. The oil can be extracted by various methods. The interest in new technologies as well as the lack of efficiency of available techniques to extract avocado oil have led to continual research on developing new extraction techniques. Avocado oil can be extracted by physical, chemical, and biological methods. New techniques to extract avocado oil need to be developed to improve overall extraction yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 73 publications
0
37
0
2
Order By: Relevance
“…It involves the use of an organic solvent (mostly hexane) as extraction agent to separate the oil from the fruit material (Rosenthal et al., 1996), although other solvents such as acetone, petroleum ether, ethyl ether, chloroform, and benzene have also been employed (Costagli & Betti, 2015; Lewis et al., 1978; Woolf et al., 2009). Currently, the extraction of avocado oil with solvents using the Soxhlet method is used as a reference with other extraction methods to compare factors such as yield and quality characteristics of the oil according to the American Oil Chemists Society and/or Codex Alimentarius (fatty acids composition, peroxide, iodine and saponification values, and specific gravity) (Nogueira‐de‐Almeida et al., 2018), and others such as refraction index, electrical conductivity, content of LSBC (Flores et al., 2019), odor, color, taste, stability, smoke point, and moisture are also considered as quality parameters (Satriana et al., 2019) (Table 2).…”
Section: Extraction Methodsmentioning
confidence: 99%
“…It involves the use of an organic solvent (mostly hexane) as extraction agent to separate the oil from the fruit material (Rosenthal et al., 1996), although other solvents such as acetone, petroleum ether, ethyl ether, chloroform, and benzene have also been employed (Costagli & Betti, 2015; Lewis et al., 1978; Woolf et al., 2009). Currently, the extraction of avocado oil with solvents using the Soxhlet method is used as a reference with other extraction methods to compare factors such as yield and quality characteristics of the oil according to the American Oil Chemists Society and/or Codex Alimentarius (fatty acids composition, peroxide, iodine and saponification values, and specific gravity) (Nogueira‐de‐Almeida et al., 2018), and others such as refraction index, electrical conductivity, content of LSBC (Flores et al., 2019), odor, color, taste, stability, smoke point, and moisture are also considered as quality parameters (Satriana et al., 2019) (Table 2).…”
Section: Extraction Methodsmentioning
confidence: 99%
“…These disadvantages have stimulated the study of novel technologies, particularly enzyme-assisted aqueous extraction [13], cold-pressed extraction [14], microwave-and ultrasound-assisted extraction (UAE) [15], high hydrostatic pressure extraction [16] and supercritical fluid extraction (SFE) [12,17]. A critical review of avocado oil extraction and refining processes can be found in Satriana et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…SFE oils 1, 2, 3 and 5 showed a high total yield (in the range 9–28%) (Table 1), superior to that obtained for SFE oils 4, 6 and 7 (in the range 0.6–5%). Yield of HE oils 1–7 showed a similar trend, however, absolute values were higher than those of the corresponding SFE oils 1–7, as also reported by other authors (Yeddes et al ., 2012; Satriana et al ., 2019). FA concentrations of SFE and HE FO, expressed as % of total FA (g %), are reported as mean values and standard deviations in Table S1 (the corresponding literature references for reported data are listed in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarity in the FA profile of SFE‐CO 2 and Soxhlet‐extracted edible oils had been observed also for anise and fennel seeds (Bettaieb Rebey et al ., 2019). Moreover, a better quality and a lower yield of SFE‐CO 2 FO than oil extracted via the Soxhlet method have been previously evidenced for avocado fruits (Satriana et al ., 2019). We clearly evidenced, by the PCA analysis, the comparable composition of SFE FO 1–7 with those obtained by conventional hexane extraction.…”
Section: Resultsmentioning
confidence: 99%